Dynamics analysis of vertical rescue vehicle-mounted hoisting system under typical working conditions - ZENG Yuexiang; YANG Zhaojian; WANG Shuping; XIE Jiacheng; WEN Yi (Gong-kuang zidonghua, 2017)
Composition and working principle of vertical rescue vehicle-mounted hoisting system were introduced. A 3D model of the system was built by use of UG, which was introduced into ADAMS to build dynamics model of the system. Wire rope tension and collision force between rescue capsule and ground of the system under typical working conditions such as no-load lowering of rescue capsule, heavy-load lifting of rescue capsule, emergency braking of rescue capsule and over lowering of wire rope were simulated, which provide theoretical basis for selection and design of the system.